The Students’ Perception towards Code-Switching and Code-Mixing in Sociolinguistic: A Case at an English Education Major - Awab Abdulloh (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2021)
This qualitative study will investigate English Education students’ opinion towards code-switching and code-mixing; both in everyday and classroom use. In this study, it will employ an open-ended (short-answered questionnaire) with 13 questions that mainly focus students of English Education class of 2016-2018. The populations were chosen because the students of 2016-2018 have attended Sociolinguistic Course during semester 3. Moreover, to gather the population, the researcher spread the link of questionnaire written in Google Form by personally contacting several people via Whats App. Based on the findings obtained from the questionnaire, it can be inferred that the 20 respondents mainly spoke 3 languages (national: Indonesian, local: Javanese, foreign: English). Furthermore, it can be concluded that 11 respondents find code-switching and code-mixing of national, local and foreign languages acceptable to be used in everyday life and classroom situation. On the contrary, 3 respondents also see code-switching and code-mixing of national, local and foreign languages annoying and disturbing to be implemented in daily communication. Meanwhile, 6 respondents perceive code-switching and code-mixing of national, local and foreign languages as neutral to be executed in everyday and classroom situation. Keywords: Sociolinguistic; Code-Switching; Code-Mixing; English Education Students